ASPEK HUKUM PERJANJIAN SEWA BELI - Krisna Putra, A. A. Putu; Mertha, I Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
In a rent-purchase agreement it is possible that the leaseholder for any reason,is unable to meet its obligations to pay the lease purchase in accordance with theagreed terms of the agreement with the seller, that he/she (the buyer) can becategorized have broken a promise or default. Therefore, this paper will explain howthe right of ownership over goods which become the object of leasing shift from theseller to the buyer. In addition, this paper also explains about the legal consequences ifthe buyer defaults lease action. So in the lease agreement the ownership status of thegoods will move from the seller to the leaseholder after the total price for the good havebeen paid in full and legal consequences for the debtor’s liability for the breach ofcontract will get a penalty or legal sanctions. The method used in this paper is thenormative method refers to the sources of law.
Keywords: Agreement, Lease-Purchase, Default, Legal Sanctions